PENGEMBANGAN MINAT BACA WARGA BELAJAR PKBM BINA WARGA MEKARJAYA MELALUI BUDAYA LITERASI - Diana Silaswati; Emas Marlina (Adiba Aisha Amira, 2025)
The problem faced by students today is the lack of interest in reading in everyday life due to the declining motivation in reading, so it is necessary to develop interest in reading for students. One of these community services is carried out at PKBM Bina Warga Mekarjaya which involves students with an equivalent package, namely 45 people consisting of elementary school equivalent or package A, junior high school equivalent or package B and high school equivalent or package C. The implementation of this community service is through a series of socialization of reading interest development, discussions, and free book distribution as an effort to facilitate students to have the desire to read.